Thermodynamic analysis of Glycerol Steam Reforming for hydrogen production with in situ hydrogen and carbon dioxide separation - Luís M. Madeira (2015)
A thermodynamic study of Glycerol Steam Reforming (GSR) for hydrogen production with in situ carbon dioxide and hydrogen (reaction products) simultaneous removal was performed. The sorption-enhanced membrane reactor (SEMR) was divided into multiple sub-Gibbs reactors and the Gibbs free energy minimization method was employed. The effects of temperature (600-800 K), molar water-to-glycerol feed ratio (WGFR) (3-9), pressure (1-5 atm) and fraction of hydrogen and carbon dioxide removal (f, 0-0.99) on the GSR process were target of investigation. A hydrogen yield (total moles of hydrogen produced/mole of reacted glycerol) very close to the stoichiometric value of 7 was obtained at 700 K, WGFR of 9, 1 atm and for f(CO2) = 0.99 and f(H2) = 0.80. This corresponds to an enhancement of 217%, 47% and 22% in terms of hydrogen yield comparatively to the traditional reactor (TR), sorption-enhanced reactor (SER) with carbon dioxide capture (f(CO2) = 0.99) and membrane reactor (MR) with hydrogen separation (f(H2) = 0.80), respectively. In terms of coke, its formation was only observed under WGFRs below the stoichiometric value of 3.